Features of decision-making on multigroup creation in regional economy - F. F. Anyurov (Путеводитель предпринимателя, 2020)
In article provisions on acceptance by subjects of the decision on multigroup creation on the basis oftheir own intentions and availability of resources and proceeding from behavior ofthe contractor are developed, provisions which influence formation of intention of the subject to enter multigroup are formulated, options of behavior ofthe subject depending on its availability of resources are allocated, models of total decisions on multigroup creation are presented. The provisions presented in work can be used at making decision on expediency of development ofprojects in the region within the private and state partnership, development and a formulation by economic subjects of the strategic directions ofdevelopment.